2020
DOI: 10.2147/ijn.s231407
|View full text |Cite
|
Sign up to set email alerts
|

<p>Improvement of Paclitaxel-Associated Adverse Reactions (ADRs) via the Use of Nano-Based Drug Delivery Systems: A Systematic Review and Network Meta-Analysis</p>

Abstract: Background: Paclitaxel is wildly used in chemotherapy, however, the adverse drug reactions (ADRs) occurred frequently. Various novel nano-based paclitaxel delivery systems were developed. The aim performed systemically review and meta-analyses to evaluate the effect adverse drug reactions (ADRs) of paclitaxel and its nano-based delivery systems. Methods: Systematically searched PubMed, Embase, Web of Science, Cochrane, Clinicalkey, Clinicaltrial.com, ASCO and ESMO. Data of adverse effect were analyzed to odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…Clinical translatability of new drugs or nanoformulations are often limited due to toxicity concerns at various stages of drug discovery and development. While efficacious, PAC is generally not well tolerated and its limitations include low solubility, and significant toxicity associated with both the drug and the solvent (Cremophor EL), including hypersensitivity reactions, bronchospasms, hypotension, hematological toxicity, periph-eral sensory neuropathy, myalgia, arthralgia and alopecia [8,45]. We have demonstrated FA-ExoPAC clearly enhanced therapeutic efficacy of PAC diminishing the dose-related toxicity issues.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Clinical translatability of new drugs or nanoformulations are often limited due to toxicity concerns at various stages of drug discovery and development. While efficacious, PAC is generally not well tolerated and its limitations include low solubility, and significant toxicity associated with both the drug and the solvent (Cremophor EL), including hypersensitivity reactions, bronchospasms, hypotension, hematological toxicity, periph-eral sensory neuropathy, myalgia, arthralgia and alopecia [8,45]. We have demonstrated FA-ExoPAC clearly enhanced therapeutic efficacy of PAC diminishing the dose-related toxicity issues.…”
Section: Discussionmentioning
confidence: 87%
“…As with many other chemo drugs, PAC exhibits poor oral bioavailability; hence, it is administered intravenously. To increase bioavailability, several drug delivery formulations of PAC have been developed, including nanoparticle albumin-bound (Abraxane ® ), liposomal (Lipusu ® ), polymeric micelles (Genexol ® PM), polymeric-drug conjugates (Xyotax™/OPAXIO) and an injection concentrate for nanodispersion (Taclantis™/Bevetex ® ), as reviewed by Chor et al [8]. Clinical translatability of these nanoformulations was impeded due to various factors like toxicity, scalability and cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugation of MHI-148 and PTX is based on a solution-phase reaction carried out between the 2′-OH group of PTX and the carboxylic group of MHI-148, in the presence of DIC and DMAP as activating agents, forming a stable 33 , 34 ester linkage ( Figure 1A ). The purification and effectual removal of unconjugated MHI-148 and PTX were performed via dialysis using the Mini Dialysis membrane (MWCO cut off 1k) in triple-distilled water for 2 days.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the extended use of paclitaxel in anti-tumor treatment, it has been reported that its administration at therapeutic concentrations (10 -6 mol/L approximately) causes adverse effects like hepatotoxicity, leukopenia, neutropenia, anemia, thrombocytopenia, neurotoxicity, vomits, alopecia, fatigue, mucositis and diarrhea[ 155 - 158 ]. In addition to the low-efficiency synthesis of paclitaxel and its side effects, another problem is its insolubility in water, which affects its bioavailability.…”
Section: Chemotherapeutic Drugs Interacting With Machrsmentioning
confidence: 99%